The political ecology of forest products in Indonesia: a history of changing adversaries - Jong, W. de; Belcher, B.; Rohadi, D.; Mustikasari, R.; Levang, P. (Kyoto University Press, 2003)
This paper look at forest products (FP) procurement and trade in Indonesia in a historical perspective, and critically investigate the nature of the actions of the players involved in these economic activities. It identifies the different actions of the various participants that can be qualified as rent-seeking, and proposes a classification of these actions in different categories. Using these different types of rent seeking allows the identification of changes in strategies used by different actors in order to increase their benefits from FP trade. Different actors had a different set of opportunities to use some actions within this set of rent-seeking actions, depending on the special circumstance of time and place in which each of the actors operates. There are some general trends in rent seeking related to FP trade. Those who had the power to do so used coersion to benefit from FP trade throughout the history of this trade in Indonesia. Collusion between traders, government officials made use of inappropriate implementation of the rule of law from central government, timber and oil palm companies claim forest territories because there is no consent on property rights have been a constant practices throughout history and are still being used today but maybe less so or more difficult during the reformasi era.